Literature Study Of The Relationship Of Husband's Support With The Event Of Depression in Postpartum Motherstitle - Sisi, Aisyah Tita Rahmayuly; Mutmainnah, Muthia; Ekawaty, Fadliyana (Program Studi Keperawatan Universitas Jambi, 2024)
Postpartum depression is a mental disorder that occurs in the first few days or weeks after giving birth. Psychiatric disorders in the form of unstable mood disorders, sadness, dysphoria and confusion with himself. Postpartum mental disorders can be mild called Baby Blues. If not treated properly, it can progress to Postpartum Depression. This study aims to determine the relationship of husband's support with the incidence of depression in postpartum mothers. This research method uses a literature study approach in the form of a literature review. Search articles using electronic based, such as Google Scholar, Researchgate and Garuda portal using Indonesian and English keywords. This is done to find articles that match the inclusion and exclusion criteria and then review the articles. There were 10 articles obtained from the screening results. the results of the analysis of the 10 articles analyzed, it was found that there was an influence of the relationship between husband's support and the incidence of depression in postpartum mothers. The justification from the results of this study is that mothers who get support from their husbands will feel comfortable, safe, respected, valued, needed, strong so that they can reduce the impact of depression on postpartum mothers. The conclusion of this study is that there is a significant relationship between the relationship of husband's support with the incidence of postpartum depression. Keywords: Postpartum Depression, Husband's Support